A PRACTICAL APPROACH TO FRACTIONAL ANALYSIS FOR FINANCE - Trần Hùng Thao; Nguyễn Tiến Dũng (Tạp chí Khoa học Đại học Đà Lạt)
This paper is a brief survey on our contributions to some important fractional models in Finance from a practical approach.